THE INFLUENCE OF JOB SATISFACTION, JOB STRESS AND CAREER DEVELOPMENT ON BARISTA TURNOVER INTENTION - Widjaya, Ardelia; Ie, Mei (Graduate Program of Universitas Tarumanagara, 2024)
Turnover intention is a form of employee assessment that has not been achieved in real terms towards the continuity of his relationship with the current employer or company. Then, the intention to move employees can be influenced by factors such as job satisfaction, job stress and career development. The purpose of this study was to determine the effect of job satisfaction, job stress and career development on turnover intetion. The sampling technique in this study uses a non-probability method with a saturated sampling technique that refers to sampling as a whole. The sample in this study were 50 baristas. The results of this study indicate that job satisfaction has a positive effect on turnover intention, job stress has a positive effect on turnover intention and career development has a positive effect on turnover intention. The implication of this research for the company in general is that the company can manage the turnover intention level of baristas through increasing job satisfaction, including by fulfilling employee rights, especially regarding better compensation.